Values embodiment of the Nyangahant ritual in Salako community's culture in Kampung Pueh, Lundu, Sarawak - Chelum, Alexander Anak; Magiman, Mohamad Maulana; Leng, Chan Siaw; Kundat, Franklin Ragai (Human Resource Management Academic Research Society, 2023)
This study depicted the values embodied in the Nyangahant ritual ingrained in the Salako community's culture in Kampung Pueh, Lundu, Sarawak. Cultural examples include human creations, tastes, intentions, and mental or intellectual things. Ritual is a culture that gives rise to traditions in which people continuously perform thoughts and actions. The Nyangahant ritual is highly valued in the Salako community because it serves as a guide in community life, creating a harmonious atmosphere and balancing the harmonious relationship between human life, the universe, and their God, Jubata. This study aims to analyse the values contained in the Nyangahant ritual implementation in the culture of the Salako community in Kampung Pueh, Lundu, Sarawak. This study employs a descriptive qualitative research method. Methods of data collection include observation, interviews, and document analysis. To analyse data, a descriptive qualitative analysis method is used, which involves reducing data, presenting data, and drawing conclusions. The research subjects are traditional leaders (Tuha Adat), chieftains (Penghulu), village heads (Ketua Kampung), cultural practitioners, and community figures. The study's findings show that the Nyangahant ritual in the Salako community's culture in Kampung Pueh, Lundu, Sarawak contains social, moral, cultural, and economic values. Material, Vital, and spiritual values are examples of social values. Aside from that, spiritual values include religious and spiritual values. At the same time, the moral values that correspond are deliberation, togetherness, obedience (Barakump), collaborative effort, and cooperation (Baaie'). The study’s findings show that, despite the various cultural assimilation effects of the modern world, the Salako community maintains traditional and cultural practices passed down from previous generations. This is due to the Salako community's beliefs, customs, and culture, which define their community identity in Kampung Pueh, Lundu, Sarawak.